Tatalaksana Oral Non-Antimikroba Pada Pasien Akne Vulgaris - Ayu Wulandari; Dwi Indria Anggraini (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2020)
Introduction: Acne vulgaris (acne) is a non-infectious skin condition that is very common and often comes in dermatological practice. Because acne often appears chronic and can last for years, safe and effective long-term therapy is needed. Given the increasingly frequent antibiotic-resistant bacteria and the severity of the consequences if there is resistance, dermatologists are needed to maximize the use of non-antimicrobial therapy when treating patients with acne. Objective: To find out which oral non-antibiotic drugs can be used for acne vulgaris therapy Method: The article was prepared using the literature review method, involving 32 literature sourced from books and journals. Results: The emergence and potential transfer of antibiotic resistance in skin microorganisms is of current concern in treatment especially in the context of dermatology where long-term treatment with antibiotics. Remarkably, non-antibiotic therapy in the form of isotretinoin - non-antimicrobial retinoids is effective in reducing or eradicating anaerobic Propionibacterium acnes that is causally involved in the pathogenesis of the Acne vulgaris complex. Discussion: In this review of the literature we present data on the effects of the proper use of non-antimicrobial therapy for acne. There are various topical and oral treatment options that can be used gradually according to the severity and therapeutic response of the patient. Non-antimicrobial treatments can be very good at controlling acne, especially when used as maintenance therapy. While antibiotics have a role in the treatment of acne, they should not be used as monotherapy, and the use of old antibiotics is not recommended. Conclusion: Some drugs whose hormonal mechanism can be oral non-antimicrobial drugs in the treatment of acne vulgaris Keywords: Acne, Antibiotics, Isotretinoin, Spironolactone, Subantimicrobial